ANALISA KERUGIAN PEMBANGKIT AKIBAT KEBOCORAN AIR MELALUI GUIDE VANE : STUDI KASUS PADA PEMBANGKIT LISTRIK TENAGA AIR BAKARU - Nur Hamzah; Muhammad Ruswandi Djalal; Muhammad Sulfajar Mas’ud (Jurnal Teknologi, 2023)
To maintain the reliability of the plant so that it continues to operate optimally, therefore the company management has arranged several scheduled maintenance activities. The result of the delay in maintenance had an impact on some equipment so that it suffered fatal damage. One of the mechanical problems that occur in PLTA BAKARU is water leakage that occurs in the guide vane. At the PLTA Bakaru unit, the impact of this guide vane leak can cause the generator to trip with an indication of 133 QBL and require the unit to leave the concession for some time. Thus the result of the disturbance becomes a loss for the company because it cannot produce electricity. From the results of the analysis, it was found that the amount of water needed to generate 1 kwh in unit 1 of PLTA Bakaru was 0.000295 m3 / s, the amount of energy loss caused by leaks in the guide vane was 121,975,031 kWh in 2015; 41,933.26 kWh in 2016; 135,591.42 kWh in 2017; and 518,637.17 kWh in 2018, power losses also occurred in the use of pumps for handling leakages of 75 kW. the amount of water consumption continued to increase from 2015 to 2018 before the overhaull and after overhaul maintenance the SWC value decreased to 0.29365 at 63 MW unit load operations.